Estate Planning: Preparing a Letter of Last Instructions - Josephine Turner; Martie Gillen (EDIS)
A letter of last instructions is one of the most helpful things you can provide for your family. The letter should express your wishes following your death so that your personal representative or family member has the information they will need about your personal and financial matters. This revised 3-page fact sheet was written by Josephine Turner and Martie Gillen, and published by the UF Department of Family, Youth and Community Sciences, December 2011.